Population structure of Brazilian Gyr dairy cattle - Reis Filho,João Cruz (2010)
The objective of the present study was to evaluate the genetic structure of Gyr cattle selected for milk production. Files of pedigree and production were composed of 27,610 animals. The ENDOG program was used for the calculation of individual inbreeding coefficient (F) and coefficient of average relatedness (AR), effective number of animals(Ne), effective number of founders (f e) and ancestors (f a), and generation interval (GI). Individual inbreeding coefficients and average relatedness in the population were 2.82% and 2.10%, respectively. It was observed a reduction in the effective number of animals, especially after publication of the results of the first progeny test. The estimated effective number of founders was 146 and 75 for the ancestrals. Out of those, only 28 ancestors accounted for the origin of 50% of the population genes. The average generation interval was 8.41 years and it was longer for males than for females. For maintaining genetic variability in future generations, it should be invested mating strategies that reduce inbreeding and which do not use massively only some high breeding value sires.